Data from: Spatiotemporal isolation of oilseed rape fields reduces insect pest pressure and crop damage - Bötzl, Fabian; Lundin, Ola (Swedish University of Agricultural Sciences, 2023)
We studied the effects of different landscape parameters on three spatial scales on the densities of pest flea beetles and crop damage at the cotyledon stage in 56 spring oilseed rape fields across five years. The landscape parameters investigated include the cover of non-crop habitats (forests and pastures) as potential overwintering sites, the distance to winter oilseed rape fields in the same year, the distance to spring oilseed rape fields in the preceding year, the landscape level crop diversity in the previous year and the edge-density in the surrounding landscapes.
Flea beetles (Coleoptera, Alticinae) were collected with four pitfall traps in one observation plot established in each field and counts represent total catches for all four traps and sampling intervals combined. Crop damage was assessed in 10 or 16 (depending on the year) 0.5 m x 0.5 m squares per observation plot following the crop damage categories in Ekbom & Kuusk (2005), https://res.slu.se/id/publ/7184, at the end of cotyledon stage (~ BBCH 14). Values represent the average crop damage per observation plot. Landscape parameters were extracted from the official land-use maps provided by Lantmäteriet (Terrängkartan) at three radii (500 m, 1000 m and 2000 m) around the centre of the observation plots.
For further information on the detailed methodology, see methods in the publication Boetzl et al. (2023) Spatiotemporal isolation of oilseed rape fields reduces insect pest pressure and crop damage. Journal of Applied Ecology.

The data in the 'combined_dataset.csv' file have information on flea beetles and crop damages recorded in 56 fields ('site_ID') and landscape parameters in the landscapes surrounding these fields at three spatial scales. 169 rows.
The landscape parameters investigated include the cover of non-crop habitats (forests and pastures) as potential overwintering sites, the distance to winter oilseed rape fields in the same year, the distance to spring oilseed rape fields in the preceding year, the landscape level crop diversity in the previous year and the edge-density in the surrounding landscapes. Flea beetles (Coleoptera, Alticinae) were collected with four pitfall traps in each plot in each field and counts represent total catches for all four traps and sampling intervals combined.

Data innehåller information om olika landskapsparametrar på tre rumsliga skalor, förekomster av jordloppor och gnagskador på groddplantor i 56 vårrapsfält under fem år. En mer detaljerad beskrivning finns på engelska.

Uppgifterna i filen "combined_dataset.csv" innehåller information om förekomst av jordloppor och skador på grödan som registrerats i 56 fält ("site_ID") och landskapsparametrar i landskapen som omger dessa fält på tre rumsliga skalor. 169 rader. En utförligare beskrivning ges på den engelska sidan.
Data från: Rumslig och tidsmässig isolering av rapsfält minskar trycket av skadeinsekter och skador på grödan
Keywords: Habitats and biotopes; Naturtyper och biotoper; Phyllotreta; Phyllotreta atra; svart jordloppa; Phyllotreta striolata; krokrandig jordloppa; Chaetocnema; Alticinae; Phyllotreta undulata; vågrandig jordloppa; Phyllotreta vittula; kornjordloppa; legacy effect; fördröjd effekt; semi-natural habitat; semi-naturliga habitat; landscape structure; landskapsstruktur; neonicotinoid ban; förbud mot neonikotinoider; flea beetles; jordloppor; Brassica napus; Brassica napus; insect pest management; bekämpning av skadeinsekter; Phyllotreta; Phyllotreta; Biological Sciences; Biologi; Ecology; Ekologi; Agricultural and Veterinary sciences; Lantbruksvetenskap och veterinärmedicin; Agricultural Science; Jordbruksvetenskap; Farming; Areella näringar; Environment; Miljö